OUTCOME OF B-LYNCH APPLICATION IN PATIENTS WITH POST-PARTUM HEMORRHAGE FOLLOWING CESAREAN SECTION - Islam, Ansa; Salma Rehman; Anisa Fawad; Humaira Jadoon; Shehla Noor; Maryam Bibi (Journal of Ayub Medical College Abbottabad, 2023)
Background: The most common cause of post partum hemorrhage after a cesarean section is uterine atony. The main aim of this study was to examine the outcomes of the B-Lynch procedure in patients who experienced primary PPH after cesarean section. Methods: This study spanned one year, from August 2020 to August 2021, at Ayub Teaching Hospital. Patients who developed post-partum hemorrhage after a cesarean section were enrolled in this study and a thorough review of their records was conducted to identify those who received B-Lynch sutures and assess the resulting outcomes. Results: Out of the 87 patients who experienced PPH, 24 (27.6%) patients received the B-Lynch procedure. Among these 24 patients, only two (8.3%) needed hysterectomy, while the remaining 22 successfully recovered after receiving the B-Lynch procedure. Conclusion: The B-Lynch technique proves to be a safe, effective, and easily applicable method for stopping hemorrhage in patients who experienced significant initial postpartum hemorrhage due to uterine atony